Hierarchy as a theme in the US college, 1880–1920. Issue 1 (2nd January 2016) - Ris, Ethan W.
Abstract : How did the undergraduate college rapidly position itself as the gateway to middle-class US employment between 1880 and 1920? This article attempts to explain one part of that process. Drawing on Weberian organisational theory, transnational intellectual history and case studies of three institutions, it identifies hierarchy as a defining aspect of both modern society and the modern workplace – one that must be comprehended and mastered by the successful 'white collar' worker. The author describes the turn-of-the-century transformation of the US college in the context of its increasingly hierarchical nature, as opposed to traditional explanations that focus on human capital production or the incorporation of the German research university model. Hierarchical structures in the hidden and extra-curriculum of the US college helped establish it as the pre-eminent testing ground for aspiring bureaucratic workers.